The Influence of Principal's Leadership Style on Teacher Performance - Badrun Badrun; Mustahiqurrahman Mustahiqurrahman; I Made Indra; Fakhrurrazi Fakhrurrazi; Muhammad Ali Akbar (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study aims to determine the influence of the principal's leadership on teacher performance. The principal's leadership style is a factor that is assumed to affect teacher performance. The application of the principal's leadership style can be assumed to influence teachers' good and bad performance. The location of this research is Madrasah Ibtidaiyah Negeri 2 Mataram. The results of this study stated that 45, 31% of principals displayed a leadership style in the outstanding category, 52,60% of principals were judged to show a good leadership style, 1,56% of principals said a leadership style in the moderate category, and 0,52 displayed a leadership style. Less category. The principal's leadership style plays a vital role in building a harmonious relationship between the principal and the teacher, improving teacher performance. Based on the analysis results, it can be concluded that the principal's leadership style can be used as a predictor variable and can determine and influence the performance of Madrasah Ibtidaiyah Negeri 2 Mataram teachers.